Cryptanalysis and Improvement of RSA-based Authentication Scheme for Telecare Medical Information Systems - Keewon Kim(김기원) (한국컴퓨터정보학회논문지, 2020)
The telecare medical information system (TMIS) supports convenient and rapid health-care services. A secure and efficient authentication and key agreement scheme for TMIS provides safeguarding electronic patient records (EPRs) and helps health care workers and medical personnel to rapidly making correct clinical decisions. Giri et al. proposed an RSA-based remote user authentication scheme using smart cards for TMIS and claimed that their scheme could resist various malicious attacks. In this paper, we point out that their scheme is still vulnerable to lost smart card attacks and replay attacks and propose an improved scheme to prevent the shortcomings. As compared with the previous authentication schemes for TMIS, the proposed scheme is more secure and practical. KCI Citation Count: 0